Regional references vs. international standards for assessing weight and length by gestational age in Lithuanian neonates - Ruta Morkuniene; Tim J. Cole; Egle Marija Jakimaviciene; Agne Bankauskiene; Jelena Isakova; Nijole Drazdiene; Vytautas Basys; Janina Tutkuviene (Frontiers Media S.A., 2023)
IntroductionThere is no global consensus as to which standards are the most appropriate for the assessment of birth weight and length. The study aimed to compare the applicability of regional and global standards to the Lithuanian newborn population by sex and gestational age, based on the prevalence of small or large for gestational age (SGA/LGA).Materials and MethodsAnalysis was performed on neonatal length and weight data obtained from the Lithuanian Medical Birth Register from 1995 to 2015 (618,235 newborns of 24-42 gestational weeks). Their distributions by gestation and sex were estimated using generalized additive models for location, scale, and shape (GAMLSS), and the results were compared with the INTERGROWTH-21st (IG-21) standard to evaluate the prevalence of SGA/LGA (10th/90th centile) at different gestational ages.ResultsThe difference in median length at term between the local reference and IG-21 was 3 cm-4 cm, while median weight at term differed by 200 g. The Lithuanian median weight at term was higher than in IG-21 by a full centile channel width, while the median length at term was higher by two channel widths. Based on the regional reference, the prevalence rates of SGA/LGA were 9.7%/10.1% for boys and 10.1%/9.9% for girls, close to the nominal 10%. Conversely, based on IG-21, the prevalence of SGA in boys/girls was less than half (4.1%/4.4%), while the prevalence of LGA was double (20.7%/19.1%).DiscussionRegional population-based neonatal references represent Lithuanian neonatal weight and length much more accurately than the global standard IG-21 which provides the prevalence rates for SGA/LGA that differ from the true values by a factor of two.